Detection Of Water Levels In Sewering Channels As Flood Disaster Early Warning System - Syah Alam; indra surjati; Lydia Sari; Sentot Novianto; Chairul Rizki; Rizka Shafira; Tri swasono adi (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
In 2020 a number of areas in DKI Jakarta were hit by floods, one of which was the North Tanjung Duren Village, Grogol Petamburan District, West Jakarta. The extreme rainfall of 377 mm/day has flooded almost all areas of DKI Jakarta and its surroundings. In addition, poor drainage causes water to stagnate, causing flooding. However, the absence of an early flood information system makes residents restless when the rainy season arrives. The Community Service (Community service activity) activity carried out aims to provide training to the community in the Tanjung Duren Utara Village area RW 04, RT 0010 regarding water level detection equipment placed in culverts. This tool serves to provide early information if the volume of water in the culvert is full of information in the form of a siren sound. The method used in this Community service activity activity is to provide online counseling and training to the community in RT 0010 / RW 04, North Tanjung Duren Village, Grogol Petamburan District, West Jakarta. The results obtained are an increase in public understanding regarding the dangers of flooding to household electricity, as indicated by the results of the pre-test and post-test which are obtained an average of 43 and 90, respectively. Public understanding of the dangers of flooding to electricity has increased up to 109.3%. In addition, the average partner satisfaction with the material presented is 92%, this shows that the material presented by the presenters team is very useful for the extension participants.